2014
DOI: 10.1371/journal.pone.0111700
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Sleep Patterns and Night-Time Technology Use: Results of the Australian Broadcasting Corporation's Big Sleep Survey

Abstract: IntroductionElectronic devices in the bedroom are broadly linked with poor sleep in adolescents. This study investigated whether there is a dose-response relationship between use of electronic devices (computers, cellphones, televisions and radios) in bed prior to sleep and adolescent sleep patterns.MethodsAdolescents aged 11–17 yrs (n = 1,184; 67.6% female) completed an Australia-wide internet survey that examined sleep patterns, sleepiness, sleep disorders, the presence of electronic devices in the bedroom a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 31 publications
6
102
1
2
Order By: Relevance
“…There is some evident that the proportion of late chronotypes has grown larger over the past decades [26,55], possibly due to the increased use of light-emitting devices such as laptops and smartphones. Their use especially in the evening, and thus exposure to blue-enriched light after dark, has been shown to be associated with melatonin suppression, and delayed circadian phase and sleep patterns [56,57]. Nevertheless, Roenneberg et al [11] found a similar age-specific chronotype profile when looking at yearly entries in their large database between 2003 and 2012, providing some evidence for an age-vs. cohort-effect.…”
Section: Limitationsmentioning
confidence: 99%
“…There is some evident that the proportion of late chronotypes has grown larger over the past decades [26,55], possibly due to the increased use of light-emitting devices such as laptops and smartphones. Their use especially in the evening, and thus exposure to blue-enriched light after dark, has been shown to be associated with melatonin suppression, and delayed circadian phase and sleep patterns [56,57]. Nevertheless, Roenneberg et al [11] found a similar age-specific chronotype profile when looking at yearly entries in their large database between 2003 and 2012, providing some evidence for an age-vs. cohort-effect.…”
Section: Limitationsmentioning
confidence: 99%
“…We know that cross-sectional studies have demonstrated associations between the amount of technology intrusion and shorter sleep durations [4][5][6]. This could represent an actual effect, or may represent activity displacement (e.g.…”
Section: This Article Is Part Of the Topical Collection On Sleep Epidmentioning
confidence: 99%
“…Secular changes in technology use are regularly cited by sleep researchers (including ourselves) as drivers of poor sleep or poor sleep behaviour, although most studies are cross sectional [4][5][6]. Cohort studies are less common [31].…”
Section: Secular Social Forces That May Drive Sleep Durationmentioning
confidence: 99%
“…8,64,65 Increased use of electronic media seems to have a similar effect. 66,67 The decrease in parentally set bedtimes has a noteworthy effect, with significantly later bedtime and shorter sleep duration in those without parent-set bedtimes. 68 Another contributing factor is working status, with adolescents who engage in employment displaying shorter sleep durations and increased daytime sleepiness compared to their non-working peers.…”
Section: Environmental Factorsmentioning
confidence: 99%